Enhancing Students’ Mathematical Critical Thinking Skills through STEM Learning on Junior High School - Pratiwi, Fresty Restu; Hendriana, Heris; Supriatna, Tatang; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
This study aims to Enhancing Students' Mathematical Critical Thinking Skills Through Stem Learning On Junior High School. Critical thinking is an essential component in mathematics education, as it equips students with the ability to solve real-world problems, analyze data, and develop deeper conceptual understanding. The study adopts a quasi-experimental design with a pretest-posttest control group, involving seventh-grade students from SMPIT Mentari Ilmu. The experimental group (VII Shofiyyah) was taught using STEM-based learning, while the control group (VII Khaula) received conventional instruction. Both groups were assessed through pretests and post-tests to evaluate improvements in critical mathematical thinking skills. The data were analyzed using descriptive statistics, normality tests, and independent t-tests to determine the significance of the results. Findings indicated that the experimental group significantly outperformed the control group, with higher post-test scores reflecting greater improvement in critical thinking skills. Moreover, the students and teachers expressed positive responses to the STEM-based approach, highlighting its effectiveness in fostering engagement and higher-order thinking. The study concludes that STEM-based learning serves as an effective pedagogical strategy for enhancing critical thinking in mathematics, making it a valuable tool for junior high school education. The results suggest that this approach should be further developed and implemented to promote students' critical thinking abilities in various educational contexts.